2018
DOI: 10.1016/j.ijdevneu.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of long‐term maternal fructose intake in rat offspring

Abstract: These results suggest a possible link between the chronic maternal metabolic stress, such as long-term fructose intake, and neurodevelopmental disturbances in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Sociability test was performed as previously described with minor modifications (Ellegood & Crawley, 2015; Erbas et al, 2018). Briefly, a Plexiglas cage (40 cm × 90 cm×40 cm) was divided into three equal regions (40 cm × 30 cm×40 cm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sociability test was performed as previously described with minor modifications (Ellegood & Crawley, 2015; Erbas et al, 2018). Briefly, a Plexiglas cage (40 cm × 90 cm×40 cm) was divided into three equal regions (40 cm × 30 cm×40 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Learning and memory performance of offspring were evaluated by passive avoidance learning (PAL) test as described previously (Erbas et al, 2018). PAL is comprised of fear‐motivated avoidance tasks in which the rat learns to refrain from stepping through a door that seems apparently safer but actually leads into a dark compartment with an electrified grid system that delivers a shock.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, neurotrophic factors such as NGF and BDNF play important roles in neuronal growth, survival, and synapse formation [33]. Nevertheless, conflicting results have been obtained about the levels of neurotrophic factors and NRG-1 in individuals with ASD (e.g., increased or unchanged levels), but these findings were based on detection in circulating peripheral blood samples [31,34,35]. In our study, we used brain tissue samples, so the levels found can be considered more representative of concentrations in a living brain.…”
Section: Discussionmentioning
confidence: 99%
“…The sociability test was performed as previously described with minor modi cations (Ellegood and Crawley, 2015;Erbas et al, 2018;Moy et al, 2004). Brie y, a Plexiglas cage (40 cm x 90 cm x 40 cm) was divided into three equal regions (40 cm x 30 cm x 40 cm).…”
Section: Behavioral Tests Three-chamber Sociability and Social Noveltmentioning
confidence: 99%
“…The open-eld test was conducted in an open-aired box with dimensions of 50 cm x 50 cm x 40 cm (Erbas et al, 2018). At the beginning of the test, rats were gently placed in the center of the box and freely explored the arena for 5 minutes.…”
Section: Open Eld Testmentioning
confidence: 99%